Membangun Mutu Pendidikan Karakter Siswa Melalui Implementasi Ajaran Tri Hita Karana - Arta Jaya, Kadek (Jurnal Penjaminan Mutu, 2019)
Building the character and character of the nation through education is absolutely necessary, starting from family education, school and society. In the family character education should be a school of love, where the family becomes a place of learning for their children who are full of love and affection from their parents. Character education through school is not merely just giving knowledge learning, but more about moral understanding, ethical values, noble character and so on. While character education in the community by imitating community leaders is exemplary by children. In the education process the implementation of the Tri Hita Karana  concept can provide an influence on learning outcomes, because one of the concepts of Tri Hita Karana  is to maintain harmony with fellow friends and obey religious orders and the teacher will be able to provide a better result in achieving cognitive aspects, psychomotor aspects, and apective aspects that are able to provide guidance for life to students. Students will become more obedient to school discipline, increase respect for teachers or older people, foster a sense of devotion to God Almighty and have a sense of care for the environment.